Improvement of Detergency Properties and Anti-Microbial Action of Biosoaps Using Saponin-Rich Extract and Α-Bisabolol Essential Oil - Nguyen, Van-Anh; Nguyen, Thi Thom; Hoang, Huu Hiep; Cao, Hong Ha (JST: Engineering And Technology For Sustainable Development, 2023)
In this study, natural ingredients were added to bio-soaps, synthesized from castor oil, a plant-derived ingredient, to improve the detergency, anti-bacterial, and stability capabilities (saponin from Soapacean fruit and essential oil of chamomile) of such soap. The saponin from soapnut fruit was extracted by an extraction process based on ethanol extraction. The saponin concentration in the extract was determined by the UV-Vis spectroscopy method. By evaluating the height and stability of the foam column, the surface tension using the Du Noüy method, and critical micelle concentrations (CMC), we looked into the efficiency of saponin in enhancing soap properties. The results show that saponin will reduce the value of CMC and, at the same time, expand the working limit of soap in brackish water and hard water (containing Mg2+ and Ca2+ ions). In addition, the presence of saponins and α-Bisabolol essential oil enhanced the anti-bacterial properties of the soap. These results expand the possibility of using natural substances in making green products that are clean and safe for humans and the environment.